STUDI BUDIDAYA JAMUR Lactarius sp. DI WAMENA, IRIAN JAYA - HID Latupapua; YB Subowo (BERITA BIOLOGI, 1998)
Research on the cultivated of mushroom of Lactarius gp.had been conducted in Wamena,Jayawijaya district of Irian Jay a. There were 6 kinds of media which consisted of 2 kinds of sawdust wood (Nothofaeus sp.and Paraserianthes falcataria).Each sawdust wood added in 3 level of nutrition (0%, 50% and 100%).The experimental design which had been used was factorial which arranged with completely randomized design by using 10 replications.The result showed that the micellia had grown on all of media.However,the fruiting body formation occured on the media which made of P.falcataria sawdust added in 0%; 50% and 100% nutrition and on the Nothofagus sp sawdust added in 100% nutrition.The highest yield of fruiting body had been showed on P. falcataria sawdust medium added in 100% nutrition.